2018
DOI: 10.1007/s00405-018-5066-5
|View full text |Cite
|
Sign up to set email alerts
|

Temporary olfactory improvement in chronic rhinosinusitis with nasal polyps after treatment

Abstract: The current evidence supports temporary olfactory improvement in CRSwNP patients which accords with the refractory nature of CRSwNP. Future treatment should aim to the continuous elimination of inflammation and promote the normal turnover of the olfactory epithelium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 84 publications
0
18
0
Order By: Relevance
“…Transient improvement of olfaction could be achieved after sinus surgery, and olfaction deteriorated with time in some eosinophilic CRS patients but was comparatively sustained well in non‐eosinophilic CRS patients 40 . The persistent elimination of inflammation, especially eosinophilic inflammation, is the target of therapeutic agents to maintain olfactory function 41 . Although oral steroids can achieve olfactory recovery, long‐term use was limited due to systemic side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Transient improvement of olfaction could be achieved after sinus surgery, and olfaction deteriorated with time in some eosinophilic CRS patients but was comparatively sustained well in non‐eosinophilic CRS patients 40 . The persistent elimination of inflammation, especially eosinophilic inflammation, is the target of therapeutic agents to maintain olfactory function 41 . Although oral steroids can achieve olfactory recovery, long‐term use was limited due to systemic side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Sinonasal olfactory dysfunction especially chronic rhinosinusitis (CRS) related olfactory dysfunction has been thoroughly studied and a series of distinct clinical features have been identified (Fokkens et al, 2020;Mullol et al, 2020). Peripheral olfactory impairment, olfactory fluctuation, steroid-dependent reverse, a substantial benefit from endoscopic sinus surgery and preserved retronasal olfactory function are the main features of CRS-related olfactory dysfunction (Apter et al, 1999;Stevens, 2001;Kohli et al, 2016a;Whitcroft et al, 2017;Ganjaei et al, 2018;Othieno et al, 2018;Wu et al, 2018Wu et al, , 2020. More importantly, analysis of olfactory subcomponent test score in patients with sinonasal olfactory dysfunction showed that odor threshold score was particularly impaired but odor discrimination and identification was relatively preserved (Whitcroft et al, 2017).…”
Section: Sinonasal Olfactory Dysfunctionmentioning
confidence: 99%
“…Several studies found correlations between olfactory cleft inflammatory cytokines/chemokines and olfactory performance in chronic rhinosinusitis patients (Yoo et al 2019). In these patients, altered levels of proinflammatory cytokines including tumor necrosis factor-alpha (TNF-α) and interleukin-6 (IL-6) in olfactory cleft mucus are associated with reduced olfactory identification scores (Wu et al 2018). Additionally, clinical studies indicate that immunodeficiencies (Magliulo et al 2019) or uncontrolled activation of immune cells occurring in autoimmune diseases (Shin et al 2019) can alter the capacity to smell, typically at the onset of disease.…”
Section: Osn Activity and Inflammation: Roles Of The Immune Systemmentioning
confidence: 99%